2022
DOI: 10.1098/rspb.2022.0391
|View full text |Cite
|
Sign up to set email alerts
|

Forest degradation limits the complementarity and quality of animal seed dispersal

Abstract: Forest degradation changes the structural heterogeneity of forests and species communities, with potential consequences for ecosystem functions including seed dispersal by frugivorous animals. While the quantity of seed dispersal may be robust towards forest degradation, changes in the effectiveness of seed dispersal through qualitative changes are poorly understood. Here, we carried out extensive field sampling on the structure of forest microhabitats, seed deposition sites and plant recruitment along three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…3 , 4 ). Our results revealed that seed dispersal by several important disperser species in the Białowieża Forest is non-random not only for the plant community as a whole 15 , but also for the seeds of individual species. Non-random seed dispersal by animals seems to be common 12 , 14 and has been observed, for instance, for bellbirds 56 , muntjacs 26 , and lemurs 57 along canopy gradients in tropical forests.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…3 , 4 ). Our results revealed that seed dispersal by several important disperser species in the Białowieża Forest is non-random not only for the plant community as a whole 15 , but also for the seeds of individual species. Non-random seed dispersal by animals seems to be common 12 , 14 and has been observed, for instance, for bellbirds 56 , muntjacs 26 , and lemurs 57 along canopy gradients in tropical forests.…”
Section: Resultsmentioning
confidence: 75%
“…The seed dispersal mutualism is an important ecosystem process that contributes to animal nutrition and the plant’s regeneration cycle 6 – 8 . In return for fruit pulp 9 , 10 , animals deposit seeds in favorable microhabitats, improve seed germination, and help plants to colonize new locations 11 – 15 . At larger scales, seed dispersal maintains meta-community dynamics 16 and helps plants to migrate 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations